2021
DOI: 10.1111/dth.14953
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of acute dermatological manifestations of the novel COVID ‐19 infection at a COVID ‐19 treatment center in Sub‐Saharan Africa

Abstract: The advent of the COVID-19 infection has led to reports on its cutaneous manifestations. [1][2][3] These reports have mostly been case reports and cases series, 4,5 with the prevalence ranging from 0.7% to 20.4%. 2,[6][7][8] Thus far, except for Morocco, there are no documented reports of the prevalence, type of dermatological manifestations nor of the temporal relationship of these lesions with the onset of COVID-19 infection in Africa nor in Nigeria.A prospective cross-sectional study of 161 polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The prevalence of cutaneous manifestations in African populations was reported in five studies conducted on the continent. In Nigeria, two studies reported 7/161 (4.35%) 23 and 11/140 (7.86%) COVID‐19 cutaneous manifestations 24 . In contrast, MIS‐A reported a high incidence of cutaneous manifestations in South Africa with 58/68 (85.3%), 25 10/20 (50%) in Kenya, 26 and Nachega et al.…”
Section: Epidemiologic Characteristics Of Covid‐19 Cutaneous Manifest...mentioning
confidence: 99%
“…The prevalence of cutaneous manifestations in African populations was reported in five studies conducted on the continent. In Nigeria, two studies reported 7/161 (4.35%) 23 and 11/140 (7.86%) COVID‐19 cutaneous manifestations 24 . In contrast, MIS‐A reported a high incidence of cutaneous manifestations in South Africa with 58/68 (85.3%), 25 10/20 (50%) in Kenya, 26 and Nachega et al.…”
Section: Epidemiologic Characteristics Of Covid‐19 Cutaneous Manifest...mentioning
confidence: 99%
“…A prospective study of 161 polymerase chain reaction COVID-19 positive patients for skin disorders was carried out. 7 All patients were examined for skin disorders with a temporal relationship with their COVID-19 illness (together with or shortly afterwards). Only seven (4.2%) patients declared new onset rash, itch or skin discoloration.…”
mentioning
confidence: 99%
“…Only seven (4.2%) patients declared new onset rash, itch or skin discoloration. 7 The skin manifestations were mostly acral in location included purpura, scaly rash, morbilliform rash, blister and urticaria. 7 Despite the paucity of skin manifestations, the authors' work is commendable, as they also report severe difficulties in conducting dermatologic clinics and limitations on training sessions for trainee doctors.…”
mentioning
confidence: 99%
See 2 more Smart Citations